Innovations in Pharmacovigilance: Leveraging Artificial Intelligence for Enhanced Drug Safety Monitoring (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The technique of pharmacovigilance, which involves keeping an eye on how medical pharmaceuticals are working after they've been approved for use, is vital in making sure that drugs are safe to use. Novel approaches brought about by the advent of Artificial Intelligence (AI) have the potential to greatly improve pharmacovigilance by making ADR identification, evaluation, and prevention much more effective. This study delves into the most recent advancements in AI-driven pharmacovigilance, shedding light on how drug safety monitoring is being revolutionised by machine learning algorithms, natural language processing, and big data analytics. In this article, we will go over the pros, cons, and possible next steps for pharmacovigilance frameworks that use AI.